(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
In the article, the authors considered the shortcomings of the formation and use of the company’s profit and its improvement in the economic activity of the company. The authors have systematized approaches to the definition of "enterprise profit", described current approaches to determining the order of formation and use of profit in accordance with the regulatory and legal framework of Ukraine. An analysis of the directions of distribution of the net profit of enterprises was carried out. The volume of profit generation by business entities in wartime conditions is analyzed. The problems of profit formation of enterprises in modern conditions of business activity are identified and the main directions of its increase are proposed.